Structural Elucidation and Molecular Docking of a Novel Antibiotic Compound from Cyanobacterium Nostoc sp. MGL001 - Niveshika,; Verma, Ekta; Mishra, Arun K.; Singh, Angad K.; Singh, Vinay K. (Frontiers in Microbiology, 2016)
Cyanobacteria are rich source of array of bioactive compounds. The present study reports a novel antibacterial bioactive compound purified from cyanobacterium Nostoc sp. MGL001 using various chromatographic techniques viz. thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). Further characterization was done using electrospray ionisation mass spectroscopy (ESIMS) and nuclear magnetic resonance (NMR) and predicted structure of bioactive compound was 9-Ethyliminomethyl-12-(morpholin - 4 - ylmethoxy) -5, 8, 13, 16 – tetraaza – hexacene - 2, 3 dicarboxylic acid (EMTAHDCA). Structure of EMTAHDCA clearly indicated that it is a novel compound that was not reported in literature or natural product database. The compound exhibited growth inhibiting effects mainly against the gram negative bacterial strains and produced maximum zone of inhibition at 150 μg/mL concentration. The compound was evaluated through in silico studies for its ability to bind 30S ribosomal fragment (PDB ID: 1YRJ, 1MWL, 1J7T and 1LC4) and OmpF porin protein (4GCP, 4GCQ and 4GCS) which are the common targets of various antibiotic drugs. Comparative molecular docking study revealed that EMTAHDCA has strong binding affinity for these selected targets in comparison to a number of most commonly used antibiotics. The ability of EMTAHDCA to bind the active sites on the proteins and 30S ribosomal fragments where the antibiotic drugs generally bind indicated that it is functionally similar to the commercially available drugs.